Randomised comparison of procedures for obtaining informed consent in clinical trials of treatment for cancer. Issue 6554 (25th October 1986) - Simes, R J; Tattersall, M H; Coates, A S; Raghavan, D; Solomon, H J; Smartt, H
Abstract : Methods of obtaining informed consent have evolved differently in Western countries without substantive information on the impact of these different practices on the patients. A randomised study was performed to compare two commonly adopted methods of seeking consent to randomised treatment: an individual approach at the discretion of each doctor and a uniform policy of total disclosure of all relevant information. The impact of both consent procedures on the patient's understanding and anxiety levels and on the doctor-patient relationship was assessed by means of a questionnaire given soon after the consent interview. Fifty seven patients were assigned at random to two groups: to 29 patients an individual approach to seeking consent was adopted and to 28 patients all relevant information was given. Seven patients refused consent to randomised treatment, with slightly more refusals by patients in the total disclosure group (5 v 2, p = 0.25). The main effects of total disclosure of all information compared with an individual approach to seeking consent were: a better understanding of treatment and side effects and of research aspects of the treatments; less willingness to agree to randomised treatment; and increased anxiety. No significant differences were found in patients' perceptions of the doctor-patient relationship. A repeat questionnaire given three to four weeks later no longer showed significant differences between the two groups.